West Nile virus - a re-emerging global threat: recent advances in vaccines and drug discovery - Kocabiyik, Deren Zehra; Álvarez, Lizdany Flórez; Durigon, Edison Luiz; Wrenger, Carsten (Frontiers in Cellular and Infection Microbiology, 2025)
West Nile virus (WNV) is an emerging mosquito-borne pathogen and is posing significant global health challenge through climate change. WNV, transmitted between birds and Culex mosquitoes, has significantly expanded northward in recent years, leading to outbreaks across Europe and North America. This review explores the recent advancements and therapeutic strategies targeting WNV’s structural and non-structural (NS) proteins, which play critical roles in viral replication and pathogenesis. Promising candidates include peptide-based inhibitors, monoclonal antibodies, and small molecules that disrupt protein-protein interactions. Most of current findings are derived from in silico methods or in vitro assays, with limited validation through in vivo studies. Although no vaccines are currently available for humans, several have been approved for horses, and development efforts are ongoing. The growing threat of WNV underscores the urgent need for validated antiviral therapies and scalable vaccines, especially considering its increasing geographic range and public health impact.